Study Of Soil Chemical Properties On Soil Banana Plants (Musa paradisiaca L) In Kalasey Village Two, Mandolang Disric Minahasa Regen - Lucy Lucy Mangamba; Diane D. Pioh; Wiesje J. N. Kumolontang (Jurnal Agroekoteknologi Terapan, 2022)
ABSTRACK Soil chemical properties greatly affect the production of banana plants (Musa paradisiaca L). If the banana plant lacks one of the nutrients it needs, it can result in inhibition of growth and production of banana plants. Nutrients Nitrogen, Phosphorus, Potassium are needed by plants for plant growth and production. Nitrogen is needed by plants in the early growth of plants. Phosphorus is needed by plants in the formation of flowers, fruit and seeds. Elemental potassium is needed as a catalyst in accelerating the process of absorption of nutrients from the soil to the plants. This study aims to determine the chemical properties of soil on soil planted with banana plants in Kalasey Dua Village, Mandolang District. From this study, it can be seen that the chemical properties of soil in the village of Kalasey Dua, Mandolang sub-district indicate that the total pH of the soil is in a neutral condition (6.3 ), C-organic has a low to moderate content value (1.35% - 2.40%). ), Nitrogen has a low to moderate content value ( 0.13% - 0.26% ), soil phosphorus has a moderate content value ( 22.12 ppm - 25.34 ppm) and Potassium is available.